Ultrasonic Studies on Binary Mixtures of Acetyl Acetone at 301K - Shaik Babu; A. Radhakrishna Murthy (E-Journal of Chemistry)
The ultrasonic velocity (U), density (ρ) and viscosity (η) measurements have been carried out for the binary mixtures of acetyl acetone with benzene, carbon tetra chloride and isoamyl alcohol at 301 K. From the measured values of ultrasonic velocity, density and viscosity, parameters such as internal pressure (πi), free volume (Vƒ) and acoustical parameters such as adiabatic compressibility (β), inter molecular free length (Lƒ), acoustic impedance (Z), relaxation time (τ) have been calculated. The results have been analyzed and interpreted in terms of molecular interactions.